‫تأثير‬‫ممارسات‬ ‫الإدارة‬ ‫البيئية‬ ‫على‬ ‫الصورة‬ ‫الذهنية‬ ‫للمنظمة‬ ‫‪‬‬‫دراسة‬‫حالة‬ ‫المؤسسة‬ ‫الوطنية‬ ‫للدهن‬ ‫فرع‬ ‫سوق‬ ‫أهراس‬ ‫‬‬ - سارة‫‪-‬‬‫معنصري‬; ‫إكرام ‫جابي‬ ‬ (My University, 2024)
The objective of this research is to examine the impact of environmental management practices on the organization of mental image by conducting a field study in an economic institution. The research has been divided into two parts, a theoretical part of which deals with the most salient concepts and practices of environmental management as well as a set of concepts and basics concerning the organization and mental image. The descriptive approach has been used in theory to identify the concepts of both environmental management practices and the mental image of the organization. In application, the descriptive method has been used to describe the results obtained and analyze them by using identification as a key research tool, which was intended for the first sample of personnel and the second sample of the components of the external environment of the organization. A set of statistical tools has been used to process the data from the two research samples and test the hypotheses. A number of conclusions have been reached, the most important of which is that there is a positive relationship between environmental management practices and the mental image of the organization and that the adoption of environmental management practices has a significant impact on the mental image of the institution in question. هدف هذا البحث إلى دراسة تأثير ممارسات الإدارة البيئية على الصورة الذهنية للمنظمة، وذلك من خلال إجراء دراسة ميدانية في مؤسسة اقتصادية، وقد تم تقسيم البحث إلى جزأين، جزء نظري تم التطرق فيه إلى أبرز المفاهيم المتعلقة بالإدارة البيئية وممارساتها ، وأيضا إلى مجموعة من المفاهيم والأساسيات المتعلقة بالصورة الذهنية للمنظمة الاقتصادية،أما الجزء الثاني فقد تمثل في الجانب التطبيقي دراسة حالة (المؤسسة الوطنية للدهن وحدة سوق أهراس). حيث تم الاعتماد على المنهج الوصفي في الجانب النظري من أجل الوقوف على المفاهيم المتعلقة بكل من ممارسات الإدارة البيئية والصورة الذهنية للمنظمة،أما في الجانب التطبيقي تم الاستعانة بالأسلوب الوصفي وذلك بوصف النتائج المتحصل عليها وتحليلها، بتوظيف الاستبانة كأداة بحثية رئيسية حيث كانت موجهة إلى عينتين العينة الأولى متمثلة في الموظفين والعينة الثانية متمثلة في مكونات المحيط الخارجي للمؤسسة، كما تم الاستعانة بمجموعة من الأدوات الإحصائية في معالجة بيانات عينتي البحث ولاختبار الفرضيات. وقد تم التوصل إلى عدد من النتائج أهمها أن هناك علاقة موجبة بين ممارسات الإدارة البيئية والصورة الذهنية للمنظمة و أن تبني ممارسات الإدارة البيئية يؤثر بشكل كبير على الصورة الذهنية للمؤسسة محل الدراسة.
Keywords: Keywords: environmental management; environmental management practices; the organization of mental image; the; الكلمات المفتاحية: الإدارة البيئية، ممارسات الإدارة البيئية، الصورة الذهنية للمنظمة، المؤسسة الوطنية للدهن وحدة سوق أهراس.